2002
DOI: 10.3928/1081-597x-20021101-11
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Sensitivity 10 Years After Epikeratoplasty

Abstract: PURPOSE: To assess corneal sensitivity in patients 10 or more years after epikeratoplasty for myopia, aphakia, hyperopia, and keratoconus. METHODS: A total of 45 eyes of 33 patients (age range at examination 33 to 55 yr) were included in the study. Corneal sensitivity thresholds using an electromagnetic aesthesiometer (Draeger) were measured at various locations on the lenticule and the recipient cornea. Measurements were evaluated regarding the corrective purpose, surgical technique, age, and gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Consequently, there is an urgent need to develop practical, long-term-storable alternatives to the use of human donor tissue, especially when the risk of disease transmission is taken into account. Furthermore, rejection of donor corneal tissue is quite high, reaching 64% at 5 years after implantation, and innervation is very slow. , The cornea is the main refractive element of the eye, and as such has several key properties and criteria essential for any artificial replacement. These criteria include high optical clarity (high light transmission and low scatter) and appropriate refractive power (controlled curvature and refractive index), adequate biocompatibility, and toughness to withstand surgical procedures and in-use wear and tear. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, there is an urgent need to develop practical, long-term-storable alternatives to the use of human donor tissue, especially when the risk of disease transmission is taken into account. Furthermore, rejection of donor corneal tissue is quite high, reaching 64% at 5 years after implantation, and innervation is very slow. , The cornea is the main refractive element of the eye, and as such has several key properties and criteria essential for any artificial replacement. These criteria include high optical clarity (high light transmission and low scatter) and appropriate refractive power (controlled curvature and refractive index), adequate biocompatibility, and toughness to withstand surgical procedures and in-use wear and tear. , …”
Section: Resultsmentioning
confidence: 99%
“…Consequently, there is an urgent need to develop practical, long-term-storable alternatives to the use of human donor tissue, especially when the risk of disease transmission is taken into account. Furthermore, rejection of donor corneal tissue is quite high, reaching 64% at 5 years after implantation, and innervation is very slow 22,23. The cornea is the main refractive element of the eye, and as such has several key properties and criteria essential for any artificial replacement.…”
mentioning
confidence: 99%
“…Subbasal epithelial nerves regenerated in 9 of 10 patients receiving implants and increased in density during the first 2 years after surgery. In other studies, nerve regeneration has been reported to be slower, occurring as late as 10 years after lamellar keratoplasty in some patients (24). Corneal nerves, situated in the anterior two-thirds of the stroma, are transected in ALK and PK procedures.…”
Section: Discussionmentioning
confidence: 96%
“…However, only 17.7% of eyes at 10 years had a normal central corneal sensitivity. 104 Epikeratoplasty may also include a centrally-placed keratectomy, but no difference in loss and recovery has been found between those patients with a keratectomy and those without.…”
Section: Tectonic Overlay Grafts and Epikeratophakiamentioning
confidence: 99%